A global value chain analysis of macroeconomic imbalances in Europe - WWWforEurope; Ederer, Stefan; Reschenhofer, Peter (Vienna, 2014)
"This paper assesses whether or to what extent the macroeconomic imbalances, which emerged in the ‘North’ and ‘South’ of the European Monetary Union before the financial and economic crisis of 2008/09, are symmetric. Firstly, we calculate bilateral exports and imports between all EU member states, applying the concept of ’trade in value added’, and discuss their role in the emergence of trade surpluses and deficits. Secondly, we decompose the changes in the trade balances into the effects of shifts in final demand on the one side and changes in the global production patterns on the other. Thirdly, we quantify to what extent an increase in domestic demand in the North and a decrease in the South would support the elimination of these imbalances. Finally, we calculate a hypothetical scenario in which final demand would expand similarly in all EMU member states. Thereby we evaluate how the macroeconomic imbalances would have evolved in the case of more balanced demand developments in the EMU in the past, as well as how adjustment could possibly happen in the future."